Evaluating the Effect of Sowing Date and Mycorrhiza on Physiological Performance and Yield of Lentil Cultivars in Dry Land Conditions in Dashtroom Yasouj Region - Hossein Shojaei-Moghadam; Mohsen Movahhedi-Dehnavi; Alireza Khoshroo; Hamidreza Balouchi; Alireza Yadavi (پژوهش‌های حبوبات ایران, 2024)
IntroductionLegumes are considered the second source of human food after cereals and have significant nutritional and agricultural values. Because of the drought resistance of lentils cultivars, dryland production of spring types could be important in the suitable regions with the proper temperature and rainfall, such as temperate regions of Yasouj county, Iran. To achieve the optimum yield of lentil using the most suitable cultivar (s) in the most proper sowing date is substantial. Mehraban (2018) reported that the highest grain yield in rainfed conditions belonged to Bilehsawar variety, which may be due to the higher weight of 1000 seeds in this variety. Also, in this research, it was found that the delay in planting by reducing the growth period and drought and heat stress in the seed filling stage causes a decrease in vegetative growth (a decrease in the branches in the plants and also a decrease in biological yield) and also a decrease in yield components such as the number of seeds. To mitigate end season drought stress in dryland lentil cultivation mycorrhizae symbiosis can be a proper practice. In a study by Piade Koohsar (2017), it was reported that the effect of mycorrhizal inoculation on grain yield in lentil plant was significant. He also reported that the highest seed yield from inoculation with mycorrhizal fungus in the Kimia variety was 1939 kg.ha-1, and the lowest seed yield was observed in the control treatment (no inoculation) in the Kalpoosh native stand at 1339 kg.ha-1. The objective of this experiment was to evaluate the effect of sowing date and mycorrhiza symbiosys on physiological and yield traits of lentil cultivars in dry land conditions in Dashtroom, Yasouj, I.R.Iran. Materials and Methods This research was carried out in 2020-2021 cropping season in the Deshtrum region, located 10 kilometers from the center of Boyar Ahmad county of Kohgiluyeh and Boyar Ahmad provinces, with average rainfall of 726 mm. The experiment performed as a split factorial based on a randomized complete block design with 3 replications. The main factor was three planting dates (January 28, February 12, and February 27) and the sub-factor was interaction of two factors including three lentil varieties (Sena, Bilehsawar, and Local accession) and mycorrhiza (Funneliformis moseae) (with and without). Leaf proline, chlorophyll, and soluble sugars content, as well as, seed nitrogen and phosphorus were measured. Plant height, grain and biological yield were measured. The data were analyzed using SAS software after performing the normality test and mean comparisons were made using the LSD test, and in the case of interaction being significant slicing was done and means compared by L.S.Means procedure. Results and DiscussionThe results showed significant effect of the triple interaction of sowing date, mycorrhiza, and cultivar on grain nitrogen percentage, total chlorophyll, leaf soluble sugars content, and biological yield. Also, the results showed that the interaction of cultivar and mycorrhiza on the plant height, grain phosphorus, total chlorophyll, the content of leaf soluble sugars, and biological yield were significant. The interaction of sowing date and variety for all studied traits except plant height were significant. Under the January 28 sowing date and mycorrhiza application, Sanna variety obtained the highest percentage of grain nitrogen (4.59%), total chlorophyll content (0.45 mg.g-1 leaf fresh weight), leaf soluble sugar content (about 120 mg.g-1 leaf fresh weight) and biological yield (3243.23 kg.ha-1) in. Also, the highest seed phosphorus percentage (1.67%), leaf proline content (13.16 µmol.g-1 leaf fresh weight), and seed yield (1152.90 kg.ha-1) related to the planting date of January 28 and Sanna variety. Application of mycorrhiza in nearly all of the traits had better performance compared with non mycorrhiza application. We saw that all cultivars had the best nutrient absorption, physiological characteristics and yield under mycorrhizal inoculation. ConclusionsThe use of mycorrhizal fungi increased all the measured traits. Also, in all three sowing dates, the variety Sanna had the highest performance in terms of the studied traits. However, the grain yield and biological yield of the January 28 sowing date were higher than other sowing dates; therefore, it can be said that the early planting (28 January) of lentil cultivars in the Dashtrum region helps the plant to achieve the maximum benefit from the growing season. On the other hand, the best result was obtained from the use of mycorrhizal fungi. According to the above conditions, the variety of Sanna along with the use of mycorrhizal fungi is the best variety for early planting in dryland conditions in the Dashtrom region.